The Delay Simulation on Hierarchical Structure for Semi-Double Track of Railway Line Using Max-Plus Algebra - Tri Utomo; Eristia Arfi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2019)
The persistently inequality of development between major cities and surrounding areas caused the displacement process, that are transport of supplies or human itself (urbanization) or commonly known as the transportation. The government has set a number of policies to overcome transportation problems, for example construct a double track railway line. This study aimed to find an alternative solution to overcome the problems of transportation, especially railway line by optimizing of using single track railway line which is given the term semi-double track using Petri Nets and Max-Plus Algebra. In the previous research, a Max-Plus algebra model has been developed based on the hierarchical structure of semi-double track railway line. In this research, the model is simulated against the problem of delay.